2018
DOI: 10.1080/1331677x.2018.1484789
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of regional inflation persistence in a C.E.E. country. The case of Poland

Abstract: This paper investigates patterns of regional inflation persistence in Poland, a representative Central and Eastern European (C.E.E.) country. This study first argues that the C.E.E. perspective is relevant in the context of this study, due to the recent transitions, incomplete processes of forming forward-looking inflation expectations and pronounced spatial inequalities. Using individual and panel regressions on disaggregate data, this study provides evidence of the aggregation bias and marked differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…In the literature, three main methodologies have been used. First, univariate autoregressive functions in the following form have often been adopted (Altissimo et al, 2007; Barsky et al., 2003; Carlos, 2004; Clark, 2006; Erceg & Levin, 2006; Gajewski, 2018; Levin & Piger, 2004; Lünneman & Matha, 2004; O'Reilly & Whelan, 2005; Tillman, 2013; Vaona & Ascari, 2012)πt=+β1πt1+β2πt2++βnπtn+εtρ=false∑i=1nβi…”
Section: Empirical Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…In the literature, three main methodologies have been used. First, univariate autoregressive functions in the following form have often been adopted (Altissimo et al, 2007; Barsky et al., 2003; Carlos, 2004; Clark, 2006; Erceg & Levin, 2006; Gajewski, 2018; Levin & Piger, 2004; Lünneman & Matha, 2004; O'Reilly & Whelan, 2005; Tillman, 2013; Vaona & Ascari, 2012)πt=+β1πt1+β2πt2++βnπtn+εtρ=false∑i=1nβi…”
Section: Empirical Analysismentioning
confidence: 99%
“…Hence, prices are shown to become more flexible over time. Gajewski (2018) analyzed 16 Polish Nuts‐2 regions over the period 2005Q1 to 2016Q3 and found that quarterly inflation persistence varied between 0.52 and 0.73. Overall, the Turkish case is roughly similar to what is observed in Italy, Korea, and Poland.…”
Section: Empirical Analysismentioning
confidence: 99%
See 3 more Smart Citations